The gene for the neuropeptide gonadotropin-releasing hormone is expressed in the mammary gland of lactating rats. - Palmon, A (1994)
The high concentration of gonadotropin-releasing hormone (GnRH) in milk of several species implies that the mammary gland is either a site of synthesis for this neuropeptide or that it is efficiently concentrated from plasma by this organ. By PCR amplification of mammary gland cDNA, we have demonstrated expression of the mRNA for GnRH. The GnRH mRNA was present in the mammary gland of pregnant and lactating rats but not of virgin rats, implying that expression of the GnRH gene is activated during pregnancy, probably by prolactin. In contrast, actin mRNA was evident in all the preparations of mammary glands. Since GnRH is also known to be synthesized by the placenta, it is likely that the placenta and the mammary gland are complementary units by which the mother exercises control over the development and the metabolism of the infant during pregnancy as well as after parturition. In addition, GnRH synthesized by the mammary gland may also affect the mother by a paracrine and/or an endocrine mechanism.